2019
DOI: 10.1186/s12884-019-2364-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential rates of cesarean delivery by maternal geographical origin: a cohort study in France

Abstract: Background: In many Western countries, higher rates of cesarean have been described among migrant women compared to natives of receiving countries. We aimed to estimate this difference comparing women originating from France and Sub-Saharan Africa (SSA), identify the clinical situations explaining most of this difference and assess whether maternal origin was independently associated with cesarean risk. Methods: The PreCARE prospective multicenter cohort study was conducted in 2010-2012 in the north Paris area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…[2][3][4] The causes for the adverse outcomes are complex but have been linked to miscommunication and misunderstandings leading to suboptimal quality of maternity care, resulting in poorer outcomes. [5][6][7] There is little knowledge of whether these disparities transfer over generations of women, but findings from Norway and the Netherlands have shown that descendants of immigrants had higher risks of stillbirth than the native populations. 8 9 With the current orientation towards patient-centred care, citizens are expected to have the ability to find and use health information, make decisions and navigate the healthcare system.…”
mentioning
confidence: 99%
“…[2][3][4] The causes for the adverse outcomes are complex but have been linked to miscommunication and misunderstandings leading to suboptimal quality of maternity care, resulting in poorer outcomes. [5][6][7] There is little knowledge of whether these disparities transfer over generations of women, but findings from Norway and the Netherlands have shown that descendants of immigrants had higher risks of stillbirth than the native populations. 8 9 With the current orientation towards patient-centred care, citizens are expected to have the ability to find and use health information, make decisions and navigate the healthcare system.…”
mentioning
confidence: 99%
“…Comparative evaluation of DRBTNP method with two existing methods such as multimodal convolutional neural network (MCNN) model designed by Petrozziello et al 2 and Robson classification method introduced by Linard et al 3 are carried out for verifying the effectiveness of the proposed research work during the pregnancy delivery mode prediction. Through the tables and graphs values, the DRBTNP method is evaluated using the following metrics.…”
Section: Resultsmentioning
confidence: 99%
“…Petrozziello et al 2 implemented Multimodal Convolutional Neural Network (MCNN) model to analyze the big available dataset for predicting the cesarean forceps or ventouse delivery using patient records. Linard et al 3 introduced Robson classification method to forecast the cesarean section or vaginal delivery using logistic regression models. However, the conventional failed to analyze more clinical risk factors for delivery prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies investigated which factors motivate women to opt for C/S [20][21][22][23][24]. The driving forces and causes of C/S are several and vary from country to country and from culture to culture [25,26]. It is important to understand the influencing factors to curb the increase in C/S rates more efficiently.…”
Section: Discussionmentioning
confidence: 99%